2010
DOI: 10.1111/j.1548-744x.2010.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Signs of the Times: Discourse Ecologies and Street Life on Oxford St., Accra

Abstract: What happens when we stop seeing streets merely as geographical locations and rather interpret them as archives? What if, in focusing on an African street such as Oxford Street in Accra, we interpret this archive not as static, but as providing a transcript of dynamic transformations of discourse ecologies? The elaboration of a method for understanding the African street as an archive of discourse ecologies will be the main subject of this paper, with a particular focus on cell phone advertising on the street … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The billboards in the area maintain bilingualism of Kiswahili and English. Perhaps this is a testimony that hybrid language is indeed used in metropolitan cities in Africa, as is the case of Dar es Salaam in Tanzania (Bwenge 2009;Higgins 2009), Cape Town in South Africa (Stroud & Mpendukana 2009) and Accra in Ghana (Quayson 2010).…”
Section: Figure 2: Monolingual Kiswahili Billboards For Church Institmentioning
confidence: 96%
See 1 more Smart Citation
“…The billboards in the area maintain bilingualism of Kiswahili and English. Perhaps this is a testimony that hybrid language is indeed used in metropolitan cities in Africa, as is the case of Dar es Salaam in Tanzania (Bwenge 2009;Higgins 2009), Cape Town in South Africa (Stroud & Mpendukana 2009) and Accra in Ghana (Quayson 2010).…”
Section: Figure 2: Monolingual Kiswahili Billboards For Church Institmentioning
confidence: 96%
“…In Kigali Rwanda, Rosendal (2010) found the adherence to the modern language regulations in main-streets, having predominantly English and French, while the shop-signs in back-streets ignore modern language rules and stick to French and Nyarwanda. In metropolitan cities such as Accra in Ghana and Cape Town in South Africa, it is found that the use of fonttype and font-colour underscores the prominence of some information given in certain languages (Stroud & Mpendukana 2009;McLaughlin 2012;Quayson 2010), in most cases hybrid language (Higgins 2009). In order to emulate previous studies, the current contribution examines the font-types and font-colour used in billboards in Orkesumet smalltownship in northern Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The literature on hawking in Africa focuses almost exclusively on urban street entrepreneurs (Agadjanian 2002; Hansen 2004, 2010; King 2006; Lyon 2007; Asiedu and Agyei-Mensah 2008; Brown et al . 2010; Quayson 2010; Klaeger 2012a, 2012b; Stasik 2013). …”
mentioning
confidence: 99%
“…This article traces the shifting geography of ‘street-level’ science work in the East African city of Kisumu by comparing two generations of local workers in public health research – one working in the present, the other remembering work and the city thirty or more years ago. Contributing to literature on the interaction of science and place – how science has shaped the city (for example, Packard 1990 ), how the city can be read as an ‘archive’ of past inscriptions (Quayson 2010 ), or how it is made part of producing and legitimizing scientific knowledge (see, for example, Gieryn 2006 ) – the article focuses on the engagement of place and work in the envisioning, and remembrance, of civic projects: the city as ‘man's method of expression’ in pursuit of association and well-being, a layered work of pasts and futures (Mumford 1961 ); or as an ensemble of movements and work that calls forth the polis, a material ‘space of appearance’ through which one's participation (or not) in a larger social entity takes form (see Arendt 1951 , 1958 : 199). 1 One's habitation and circulation in a city reflect and shape how (indeed, whether) one experiences the city as a civitas , and oneself as a citizen with entitlements and responsibilities.…”
mentioning
confidence: 99%